Education and implementation of quality management system to improve service quality in regional hospitals - Fajarini; Paramarta, Vip; Kosasih; Yuliaty, Farida; Fitriana (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2025)
The implementation of quality management systems in regional hospitals remains a challenge due to limited resources, lack of structured training, and inconsistent adherence to accreditation standards. This community service program aimed to enhance healthcare service quality by providing education and mentoring on quality management systems. The program was conducted in a regional hospital, involving 15 participants, including management, medical personnel, and administrative staff. It consisted of five key stages: preparation, socialization, training, monitoring and evaluation, and sustainability efforts. Observations indicated improvements in standard operating procedure (SOP) compliance, patient safety awareness, and documentation practices. Despite these positive developments, challenges such as resistance to change, infrastructure constraints, and limited hospital resources were observed. To ensure long-term impact, hospitals should establish quality assurance teams, integrate digital monitoring tools, and provide continuous training for healthcare workers. However, this study is limited in its ability to quantitatively measure long-term patient outcomes and service efficiency. Future research should assess measurable indicators, such as patient safety incidents and hospital performance metrics, to evaluate the broader impact of quality management system implementation in regional hospitals.